The Fundamental Analysis of Indonesian Stock Return (Case Study: Listed Public Companies in Sub-Sector Food and Beverage for the Period 2003-2012) - Khotimah, Khusnul; Murtaqi, Isrochmani (Journal of Business and Management, 2015)
Abstract. Indonesia stock market which reflected by IHSG grows extraordinary and stable for the last decade with average growth 28.67 % per year. Despite of stable growth of Indonesia economy, not all companies’ performance have similar good condition. Investigation of company’s performance especially fundamental analysis is needed to make sure that the investment is promising and can run for long term. In this investigation, Current Ratio, Book to Market, and Total Asset Turnover are used as fundamental factor affecting stock return. Using multiple regression method, these ratios are analyzed to determine which financial factors affect stock return. The result shows that Current Ratio, Book to Market, and Total Asset Turnover give significant effects to stock return. The relationship of these independent variables with stock return are negative for current ratio but positive for both Book to Market and Total Asset Turnover. This result explains that financial ratio especially Book to Market and Total Asset Turnover are indeed useful in making decision on investment and have same level of interest with other ratios. This research also exposes the possibility of other factors besides company’s financial performance affect the movement of firm’s stock price which lead to stock return. Therefore, the author suggest to conduct further research uses other macro level variables which can influence stock return such as money supply, economic growth (GDP), and inflation. Keywords: Fundamental Analysis, Stock Return, Financial Ratios, Multiple RegressionCategory: Finance